1999
DOI: 10.1111/j.1539-6924.1999.tb01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Dose‐Response Modeling of Epidemiological Data on Worker Exposures to Aldrin and Dieldrin

Abstract: The paper applies classical statistical principles to yield new tools for risk assessment and makes new use of epidemiological data for human risk assessment. An extensive clinical and epidemiological study of workers engaged in the manufacturing and formulation of aldrin and dieldrin provides occupational hygiene and biological monitoring data on individual exposures over the years of employment and provides unusually accurate measures of individual lifetime average daily doses. In the cancer dose-response mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This could be a chance finding, because recent reviews have suggested that aldrin is unlikely to have significant carcinogenic potential (IARC 1987;Sielken et al 1999;Stevenson et al 1999). This finding should be interpreted with caution given the lack of evidence of carcinogenicity, and lack of associations between other specific pesticide exposures and childhood cancer in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a chance finding, because recent reviews have suggested that aldrin is unlikely to have significant carcinogenic potential (IARC 1987;Sielken et al 1999;Stevenson et al 1999). This finding should be interpreted with caution given the lack of evidence of carcinogenicity, and lack of associations between other specific pesticide exposures and childhood cancer in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that over 75% of the cohort had dieldrin exposure levels that exceeded the assumed human equivalent dose rate corresponding to the lowest positive dose rate for female mice in a cancer bioassay in which the incidence of liver tumors had doubled. Sielken et al (1999), based on an earlier study of this cohort, have reported a cancer risk assessment for dieldrin and aldrin. The overall mortality for cancer of that study was slightly lower than the Dutch general population (46 observed deaths with an SMR of 96.8, 95% CI = 71-129).…”
Section: Discussionmentioning
confidence: 99%